The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/jom.0000000000000954
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Respiratory Effects of Air Pollution in a Panel Study of Outdoor Physical Activity and Health in Rural Older Adults

Abstract: Objective:To examine cardio-respiratory effects of air pollution in rural older adults exercising outdoors.Methods:Adults 55 and over completed measurements of blood pressure, peak expiratory flow and oximetry daily, and of heart rate variability, endothelial function, spirometry, fraction of exhaled nitric oxide and urinary oxidative stress markers weekly, before and after outdoor exercise, for 10 weeks. Data were analyzed using linear mixed effect models.Results:Pooled estimates combining 2013 (n = 36 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 48 publications
(54 reference statements)
3
27
0
Order By: Relevance
“…studies of summer and winter outdoor physical activity in older adults conducted in a predominantly rural area and small northern industrial city, respectively (Stieb et al 2017(Stieb et al , 2018. These findings provided evidence supporting the utility of the AQHI in predicting health risks for diverse health outcomes and types of communities not accounted for in developing the AQHI, which was based on the effects of air pollution on mortality in large urban centres.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…studies of summer and winter outdoor physical activity in older adults conducted in a predominantly rural area and small northern industrial city, respectively (Stieb et al 2017(Stieb et al , 2018. These findings provided evidence supporting the utility of the AQHI in predicting health risks for diverse health outcomes and types of communities not accounted for in developing the AQHI, which was based on the effects of air pollution on mortality in large urban centres.…”
Section: Introductionmentioning
confidence: 67%
“…We accounted for effects of time (trend and temporal cycles) using a linear function of time and day of week variables. In a previous study, we found no consistent associations with subdaily air pollution exposures in the hours prior to health measures (Stieb et al 2017), thus only daily 3-h maximum exposures (daily maximum of 3-h trailing averages) were considered. Air pollution variables were entered into models at individual lags of 0-2 days, each with natural spline functions of temperature with 3 degrees of freedom at individual lags of 0-2 days (9 models per pollutant).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The acute effects of air pollutants have been demonstrated repeatedly in respiratory [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and cardiovascular patients [16][17][18][19][20][21]. Such panel studies have been performed in the elderly [22][23][24][25] and in areas with high air pollution [1,14,[26][27][28][29][30], but less so in young and healthy people in settings with moderate to low air pollution levels [31][32][33][34][35][36][37][38][39]. We recruited healthy students from Vienna to study the physiological reactions of the cardiovascular and respiratory systems when exposed to everyday urban air pollution.…”
Section: Introductionmentioning
confidence: 99%